Techno-Economic Feasibility Assessment of Solar PV Water Pumping System In Dryland: Case Study In Madura - Amir, Nizar (Universitas Trunojoyo Madura, 2021)
Indonesia has enormous solar radiation potential, and it can be converted to electrical energy by utilizing solar PV systems. Mainly the irrigation of paddy rice fields in Indonesia dependent on a diesel-powered water pumping system. A solar PV system can replace this method, and it generates several benefits. The present study proposed the utilization of a solar PV system to drive the water pump based on a 100% renewable power supply. The technological and economic viability assessment of solar PV water pumping system to irrigate paddy rice filed at Telang village, Bangkalan, Indonesia, is investigated. The HOMER software has been used to generate the optimal configuration of a renewable system. Initial capital, net present cost, and cost of energy will evaluate as economic assessment criteria. The solar PV and diesel generator water pumping system also compared. The results showed that for water pumping systems, a solar PV system is more cost-effective than a diesel generator. It has lower annual operational and maintenance costs, 100% renewable energy penetration, and free energy cost.